HUBUNGAN ANTARA MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SDN 3 JATIMULYO - Nureva Nureva; Susi Mariyana (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
One factor that influences learning outcomes is interest. In learning activities, if students have an interest in learning, they will feel that learning is very important so they try to focus their attention on things related to learning activities and are happy to do it without coercion from anyone. This research aims to determine the correlation of interest in learning with mathematics learning outcomes of students at Elementary School 3 Jatimulyo, Jatiagung District, South Lampung Regency. This research uses quantitative methods and the type of correlation research. The population of this study was all fourth grade students of Elementary School 3 Jatimulyo. The sample of this study was 69 students. Data collection techniques using questionnaires and documentation. Data analysis uses the product moment correlation formula. The results of this study indicate there is a relationship between learning interest with learning outcomes in mathematics. These results are based on statistical calculations that show a calculation of 0.918> rtable 0.235. The results of the hypothesis analysis can be concluded that there is a positive correlation between learning interest and mathematics learning outcomes of fourth grade students of Elementary School 3 Jatimulyo Odd Semester Academic Year 2018/2019 by judging from the count criteria> rtable